Coagulopathies among Patients of Diabetes Mellitus in Gujrat, Pakistan - Noor Fatima, Hannana Maryam, Abid Ali, Mahnoor Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the behavior of coagulation-related tests like prothrombin time (PT) and activated partial thromboplastin time (APTT) in chronic diabetic patients. Study Design: Cross-sectional study Place and Duration of Study: Department of Hematology, Aziz Bhatti Hospital, Gujrat, Pakistan from 1st July 2022 to 31stDecember 2022. Methodology: One hundred and seventy nine patients were enrolled. Prothrombin time and activated partial Thromboplastin time were performed from the patient’s samples. Results: Forty four patients were with good glycemic control and 135 were with poor glycemic control. It was revealed that patients with type 2 diabetes with poor glycemic control had lower levels of PT concentration 10.95±1.67 and prothrombin time was 11.50±1.331 in good glycemic control patients (P=0.04).APTT result was insignificant with 33.40±2.889 in poor glycemic control patients and while in good glycemic control APTT 34.08±1.348 (p=0.389). Conclusion: Prothrombin time was low if diabetes is uncontrolled. Early detection of lower PT may indicate that micro or macrovascular coagulopathies are in progress. APTT analysis shows insignificant results in diabetic patients and did not find a special role in coagulopathies disorders. Keywords: Coagulopathies, Prothrombin time, Activated partial thromboplastin time, Chronic diabetic patients